Uncovering the Origins of the Gresik Bandeng Market as an Ancestral Heritage That Remains Alive - Dwiyan Adji Masduki (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The Bandeng Market in Gresik is an annual tradition held before Eid al-Fitr, starting on the 25th night of Ramadan until the last night. This tradition has its roots in the spread of Islam by Sunan Giri in the 15th century, which aimed to fulfill the needs of students at the Giri Kedaton Islamic Boarding School. Milkfish became a typical souvenir brought home by students from various regions. Pasar Bandeng developed into a center for buying and selling milkfish, which is not only a culinary symbol, but also a social interaction within the Gresik community. Over time, Pasar Bandeng has undergone changes due to urban development that has reduced pond land, but this tradition is still maintained through various activities such as milkfish contests and auctions. The plan to establish a milkfish village in Ujung Pangkah, although not yet fully realized, aims to preserve this tradition by managing milkfish from upstream to downstream.